Identifikasi Komoditas Unggulan Sektor Pertanian Tanaman Pangan di Wilayah Kabupaten Banyumas - Emmy Saraswati; Endang Sri Gunawati; Asteria Pudyantini (EKO-REGIONAL, 2006)
This research tries to identify any well food farming commodities in Banyumas Regency by several methods; MRP, overlay classification, Klassen Typology, and BANGDA (resources, labor, environmental impact, market, and technology) aspects. This research shows that no entirely food farming commodities in every area have well commodities potency. Paddy field farming is superior in 10 district (Wangon, Jati Lawang, rawalo, Somagede, Purwojati, Ajibarang, Pakuncen, Kedung banteng, Kembaran and North Purwokerto). Paddy no-field farming is suitable in 10 districts (Wangon, Rawalo, Kebasen, Somagede, Kalibagor, Banyumas, Ajibarang, Gumelar, Pakuncen, and Kedung Banteng). Corn farming is suitable to be cultivated in 15 districts ((Jati Lawang, Kebasen, Kemranjen, Sumpiuh, Tambak, Somagede, Kalibagor, Banyumas, Patik Raja, Pekuncen, Karang Lewas, Kedung Banteng, Baturaden, Kembaran Dan Purwokerto Timur). Soybean is well for plantation in 15 districts area (Lumbir, Jati Lawang, Rawalo, Kebasen, Tambak, Somagede, Kalibagor, Patik Raja, Ajibarang, Gumelar, Karang Lewas, Kedung Banteng, Purwokerto Barat, Purwokerto Timur Dan Purwokerto Utara). Batata farming is suitable in 15 districts area ((Wangon, Jati Lawang, Rawalo, Tambak, Banyumas, Patik Raja, Aji Barang, Pekuncen, Cilongok, Karang Lewas, Kedung Banteng, Baturaden, Purwokerto Selatan, Purwokerto Utara). Cassava is well for plantation in 10 districs (Wangon, Kebasen, Sumpiuh, Somagede, Kali Bagor, Ajibarang, Gumelar, Cilongok, Karang Lewas, Dan Kedung Banteng). Peanut farming is suitable in 19 districs (Lumbir, Wangon, Jatilawang, Rawalo, Kemranjen, Sumpiuh, Tambak, Somagede, Banyumas, Patik Raja, Purwojati, Gumelar, Cilongok, Baturaden, Sumbang, Kembaran, Purwokerto Selatan, Purwokerto Barat, Purwokerto Utara). The potencial commodities to cultivate have dominan characteristic, well contribution sides, and relatively have high BANGDA index (range 21 to  25).Keywords; ; Overlay classification, Klassen Typology, BANGDA aspects